Dispersal capacities of pollen, seeds and spores: insights from comparative analyses of spatial genetic structures in bryophytes and spermatophytes - Fichant, T.; Ledent, A.; Collart, F.; Vanderpoorten, A. (Frontiers in Plant Science, 2023)
Introduction The dramatic fluctuations of climate conditions since the late Tertiary era have resulted in major species range shifts. These movements were conditioned by geographic barriers and species dispersal capacities. In land plants, gene flow occurs through the movement of male gametes (sperm cells, pollen grains), which carry nDNA, and diaspores (spores, seeds), which carry both cpDNA and nDNA, making them an ideal model to compare the imprints of past climate change on the spatial genetic structures of different genomic compartments. Based on a meta-analysis of cpDNA and nDNA sequence data in western Europe, we test the hypotheses that nDNA genetic structures are similar in bryophytes and spermatophytes due to the similar size of spores and pollen grains, whereas genetic structures derived from the analysis of cpDNA are significantly stronger in spermatophytes than in bryophytes due to the substantially larger size of seeds as compared to spores. Methods Sequence data at 1-4 loci were retrieved for 11 bryophyte and 17 spermatophyte species across their entire European range. Genetic structures between and within southern and northern populations were analyzed through F and N statistics and Mantel tests. Results and discussion Gst and Nst between southern and northern Europe derived from cpDNA were significantly higher, and the proportion of significant tests was higher in spermatophytes than in bryophytes. This suggests that in the latter, migrations across mountain ranges were sufficient to maintain a homogenous allelic structure across Europe, evidencing the minor role played by mountain ranges in bryophyte migrations. With nDNA, patterns of genetic structure did not significantly differ between bryophytes and spermatophytes, in line with the hypothesis that spores and pollen grains exhibit similar dispersal capacities due to their size similarity. Stronger levels of genetic differentiation between southern and northern Europe, and within southern Europe, in spermatophytes than in bryophytes, caused by higher long-distance dispersal capacities of spores as compared to seeds, may account for the strikingly higher levels of endemism in spermatophytes than in bryophytes in the Mediterranean biodiversity hotspot.